Accessible or not? That is the question! Analyzing the accessibility of the historic touristic city center of Paraty (RJ) - Rodrigues, Luciana; Cheibub, Bernardo Lazary (Revista Turismo em Análise, 2020)
Paraty is a city in Rio de Janeiro, known for its natural, historical and cultural heritage, which has been recently inscribed on the World Heritage List as a Mixed Site, but it seems that it does not allow all kinds of people to visit it safely and autonomously when it comes to accessibility. Thus, this article was aimed to investigate the barriers to mobility in the Historical Center and its surroundings, specially of disabled people, as well as to analyse if there is a paradox between heritage and accessibility. From a qualitative, exploratory and descriptive research, which took place in 2018 and 2019: some techniques of Ethnographic Based Methodology were used, such as direct observations of researchers in field work, semi-structured interviews conducted with some representatives from the National Historic and Artistic Heritage Institute (IPHAN), from the Tourism and Urbanism Departments of Paraty, and the monitoring of the tourist experience of a disabled person in the Historical Center (participant observation). Furthermore, there have been examined documents, federal and municipal legislation about the accessibility in built environment and in cultural heritage sites. The results showed that there are different types of barriers in the city, though there is no legal prohibition to implement accessibility in heritage sites. It was concluded that in Paraty there is lack of effective actions by the government to reduce or extinguish several obstacles which impede full physical and spatial mobility of disabled people, mainly in the Historical Center and its surroundings.